The conference of the birds : the fifth novel of Miss Peregrine's peculiar children - Riggs, Ransom (Dutton Books, 2020)
On his deathbed, H sends Jacob Portman on a mission to make sure the peculiar Noor Pradesh get safely to an operative known only as V. Noor is the subject of an ancient prophecy about a coming apocalypse. With only a few clues and time running out, Jacob must figure out how to find the mysterious and powerful V--who doesn't want to be found.